Splicing of designer exons reveals unexpected complexity in pre-mRNA splicing - Zhang, Xiang H.-F. (Cold Spring Harbor Laboratory Press, 2009)
Pre-messengerRNA (mRNA) splicing requires the accurate recognition of splice sites by the cellular RNA processing machinery. In addition to sequences that comprise the branchpoint and the 3′ and 5′ splice sites, the cellular splicing machinery relies on additional information in the form of exonic and intronic splicing enhancer and silencer sequences. The high abundance of these motifs makes it difficult to investigate their effects using standard genetic perturbations, since their disruption often leads to the formation of yet new elements. To lessen this problem, we have designed synthetic exons comprised of multiple copies of a single prototypical exonic enhancer and a single prototypical exonic silencer sequence separated by neutral spacer sequences. The spacer sequences buffer the exon against the formation of new elements as the number and order of the original elements are varied. Over 100 such designer exons were constructed by random ligation of enhancer, silencer, and neutral elements. Each exon was positioned as the central exon in a 3-exon minigene and tested for exon inclusion after transient transfection. The level of inclusion of the test exons was seen to be dependent on the provision of enhancers and could be decreased by the provision of silencers. In general, there was a good quantitative correlation between the proportion of enhancers and splicing. However, widely varying inclusion levels could be produced by different permutations of the enhancer and silencer elements, indicating that even in this simplified system splicing decisions rest on complex interplays of yet to be determined parameters.